The impact of centralization on pharmaceutical procurement prices: the role of institutional quality and corruption. Issue 3 (4th March 2017) - Baldi, Simona; Vannoni, Davide
ABSTRACT: The impact of centralization on pharmaceutical procurement prices: the role of institutional quality and corruption. Regional Studies. This paper deals with the open issue regarding centralized versus decentralized public procurement strategy. Using a unique dataset on tender prices of selected drugs for hospital usage provided by a sample of 52 Italian local health service providers ( aziende sanitarie locali – ASLs) between 2009 and 2012, the paper tests which procurement system (centralized, decentralized or hybrid) performs better. Controlling for several covariates, including measures of institutional quality and corruption, it finds that centralized and hybrid procurers pay lower prices than decentralized units. Moreover, the results show that in areas in which institutional quality is lower or corruption is higher, the effect of centralization in terms of negotiating lower prices is much stronger, with savings of up to 60% of the price paid by ASLs that procure independently.